Association of serum vitamin D levels and simple febrile seizures in children - Adnan, Mohammad Ahad; Hossain, Mohammad Iqbal; Khanam, Wahida; Mawa, Jannatul; Ahmed, Ifthakhar; Mondol, M. Tariqul Islam (International Journal of Contemporary Pediatrics, 2023)
Background: Febrile seizure is one of the commonest childhood neurologic diseases. There is an increasing concern that vitamin D deficiency may play an etiological role. This study was conducted to find out the association between vitamin D levels and febrile seizure. Objective were to determine the association of vitamin D levels in children with simple febrile seizure. Methods: This case control study was conducted in institute of child and mother health, Dhaka from July 2019 to June 2020. Children aged six to sixty months with simple febrile seizure were ‘cases’ and those having fever without seizure were controls. Detailed history regarding breastfeeding, intake of calcium and vitamin D rich diet, sunlight exposure, family history of seizure was taken and physical examinations were done. Data collection was done through a pretested structured questionnaire. Serum vitamin D level was measured. Results: There were 44 cases of simple febrile seizure and 50 controls. Mean age of the study participants was 16.5±8.9 and 14.4±7.1 months in case group and control group respectively, with a majority in the age group 6-12 months. 34.1% of cases and 22% of controls had deficient vitamin D while 50% of cases and 34% of controls had insufficient vitamin D, respectively. Reduced vitamin D level was more common in case group. Mean vitamin D level was also significantly lower in case group. Conclusions: Decreased vitamin D level was found to be significantly associated with simple febrile seizure.